Cesarean Section and Maternal-fetal Mortality Rates in Nigeria: An Ecological Lens into the Last Decade - Hadiza Galadanci, MBBS, MSc, FWACS FRCOG; Deepa Dongarwar, MS; Wolfgang Künzel, FRCOG, FEBCOG; Oladapo Shittu, MBBS, FWACS; Murtala Yusuf, MBBS, FWACS; Sadiq Abdurrahman, NCE; Dolapo Lufadeju, PhD, FICM, CMC; Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2020)
Background or Objectives: Despite the global decline in maternal mortality within the last decade, women continue to die excessively from pregnancy-related complicationsin developing countries. We assessed the trends in maternal mortality, fetal mortality and cesarean section (C-Section) rates within 25 selected Nigerian hospitals over the last decade. Methods: Basic obstetric data on all deliveries were routinely collected by midwives using the maternity record book developed for the project in all the participating hospitals. Trends of C-Section Rates (CSR), Maternal Mortality Rates (MMR), Fetal Mortality Rates (FMR) and Spontaneous Vaginal Delivery rates (SVD) were calculated using joinpoint regression models. Results: The annual average percent change in CSR was 12.2%, which was statistically significant, indicating a rise in CSR over the decade of the study. There was a noticeable fall in MMR from a zenith of about 1,868 per 100,000 at baseline down to 1,315/100,000 by the end of the study period, representing a relative drop in MMR of about 30%. An average annual drop of 3.8% in FMR and 1.5% drop in SVD over time were noted over the course of the study period. Conclusion and Global Health Implications: We observed an overall CSR of 10.4% and a significant rise in CSR over the 9-year period (2008-2016) of about 108% across hospital facilities in Nigeria. Despite the decrease in MMR, it was still high compared to the global average of 546 maternal deaths per 100 000 livebirths. The FMR was also high compared with the global average. The MMR found in this study clearly indicates that Nigeria is far behind in making progress toward achieving the Sustainable Development Goal 3 (SGD 3) which aims to reduce the global MMR to less than 70 per 100 000 live births by 2030. Key words: • Cesarean section • Maternal mortality • Fetal mortality • Spontaneous vaginal delivery • Trends in MMR • Nigeria   Copyright © 2020 Galadanci et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.